CP-violating decays of the pseudoscalars η and η′ and their connection to the electric dipole moment of the neutron - Gutsche Th. Thomas; Blin A. H. Astrid Hiller; Kovalenko S. Sergey; Kuleshov S. V. Sergey Vasiljevich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Vacas M. J. V. Manuel J. Vicente; Zhevlakov A. S. Aleksey Seregeevich (2017, 2017)
Title screen